2013
DOI: 10.1002/nme.4603
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional brittle fracture: configurational-force-driven crack propagation

Abstract: SUMMARY This paper presents a computational framework for quasi‐static brittle fracture in three‐dimensional solids. The paper sets out the theoretical basis for determining the initiation and direction of propagating cracks based on the concept of configurational mechanics, consistent with Griffith's theory. Resolution of the propagating crack by the FEM is achieved by restricting cracks to element faces and adapting the mesh to align it with the predicted crack direction. A local mesh improvement procedure i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 22 publications
(58 reference statements)
1
54
0
Order By: Relevance
“…However, as previously noticed in the literature [31,34,10,37], we also observed that the crack path is very sensitive to small changes in geometry and loading, or to changes in the regularization parameter . Figure 19 shows changes in the final fracture geometry (isovolume renderings of the fracture field 0.9 ≤ α ≤ 1.0) and the final deformed geometry for three different values of .…”
Section: The Brokenshire Torsion Experimentssupporting
confidence: 67%
See 1 more Smart Citation
“…However, as previously noticed in the literature [31,34,10,37], we also observed that the crack path is very sensitive to small changes in geometry and loading, or to changes in the regularization parameter . Figure 19 shows changes in the final fracture geometry (isovolume renderings of the fracture field 0.9 ≤ α ≤ 1.0) and the final deformed geometry for three different values of .…”
Section: The Brokenshire Torsion Experimentssupporting
confidence: 67%
“…We finally focussed our attention on a fully three-dimensional problem initially presented in [24] and previously investigated in a number of articles [31,34,10,37]. The Brokenshire test consists of a specimen with a 45 • oblique notch subject to a torsional load (see Figure 17 for a schematic description of the domain geometry).…”
Section: The Brokenshire Torsion Experimentsmentioning
confidence: 99%
“…Later, Areias and Belytschko [21] and Duan et al [58] studied it using extended finite elements. Recently, Kaczmarczyk et al [59] solved the problem with a configurational mechanics method, consistent with Griffith's theory.…”
Section: D Pullout Testmentioning
confidence: 99%
“…Cohesive crack methodology has been widely used by many researchers for stochastic analyses of fracture propagation, eg, in which cohesive elements are inserted between element edges. If crack paths are unknown a priori, local r‐adaptivity and mesh‐realignment techniques are required to resolve mesh dependency issues . This can lead to high computational cost, particularly if Monte Carlo (MC) simulation approach is employed.…”
Section: Introductionmentioning
confidence: 99%
“…If crack paths are unknown a priori, local r-adaptivity and mesh-realignment techniques are required to resolve mesh dependency issues. 13 This can lead to high computational cost, particularly if Monte Carlo (MC) simulation approach is employed.…”
Section: Introductionmentioning
confidence: 99%